A Study on Undergraduate Medical Students’ Knowledge Perception and Awareness about Monkeypox Infection - Farheen Zehra, Waseem Sarwar, S. M. Hasan Naqvi, Ali Ahmad, Malik Armaghan Ali, Taha Hassan Habib, Aiza Khalid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Monkeypox virus infection is emerging as global outbreak in 2022. Basic knowledge about the disease, its transmission, clinical features and prevention should be provided to all healthcare providers. Aim: To assess knowledge of undergraduate medical students about Monkeypox infection. Methods: This cross-sectional study was conducted at Niazi Medical and Dental College, Sargodha between August and September 2022. Students from third to final year were included and a self-report questionnaire comprising of demographic data, source of information about infection and preventive measures based on obtainable facts from the United States Centers for Disease Control and Prevention and WHO was used.Descriptive statistical analysis was done on SPSS version 22. Results: 95.4% of participants knew about monkeypox infection out of which 87.9% reported virus as causative agent.45.4% stated direct contact as a mode of disease transmission.Two-fourth respondents didn’t know about the incubation period out of them majority were in final year.Majority learned about it through social media and most common reported symptoms were rash and fever. 34.5% were aware of the pre-emptive measures of the disease while only 1/3rd of participants were acquainted with availability of vaccine.One-fourth MBBS students, majority final year, had knowledge regarding active cases of Monkeypox in Pakistan. 2/3rd responders thought that Pakistan’s health system could not bear the burden of another outbreak. Conclusion: Knowledge of emerging monkeypox infection is limited in medical students, therefore, measures should be taken to arrange awareness programs and educational courses at institution and national levels. Keywords: Monkeypox, virus infection, global outbreak, incubation period, pre-emptive measures, medical student.